Correction of anterior crossbite of dental origin and gingival recession in early mixed dentition. Case report - Andrea Virginia González Carfora; Vanessa Halley Teixeira Gonzále; Aida Carolina Medina Díaz (Asociación Latinoamericana de Odontopediatría, 2019)
Introduction: Anterior cross-bite occurs when maxillary incisors occlude lingually to the mandibular incisors, which may be of dental or skeletal origin. The early correction of this malocclusion favors a correct interincisive relationship, allowing adequate growth and development in the sagittal direction of the maxillofacial complex. Case Report: 8 year-old male presented with cephalometric diagnosis of Class I and dental relation of Class I type 3, retruded maxillary incisors and anterior cross-bite. Presented gingival recession in vestibular gingiva of 41 and 31 Treatment was performed with removable appliance, posterior bite planes, expansion screw and Eschler arch. 16 month follow-up was performed obtaining and proper overjet, proclination of incisors and dental arch conformation. Conclusions: Dental anterior cross-bite may be successfully treated in the early mixed dentition with simple appliances.